Removal of gas-phase elemental mercury by iodine- and chlorine-impregnated activated carbons - Lee, SF; Seo, YC; Jurng, J; Lee, TG (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Gas-phase Hg-0 adsorption experiments were carried out using iodine (I)- and chorine (Cl)-impregnated granular activated carbons in a laboratory-scale fixed-bed reactor. To verify the effect of chemical loading contents on removal of mercury, different concentrations of chemicals such as KI and HCl were applied. In addition, two types of impregnated activated carbons (ACs) were tested at different temperature conditions. The characteristics of impregnated ACs were analyzed using scanning electron microscopy/energy-dispersive spectroscopy for surface morphology and chemical contents. BET analysis for surface area and X-ray spectroscopy for identification of mercury compounds on the carbon surface were conducted. Hg-0 removal efficiency increased with temperature in the case of I-impregnated ACs, while the removal efficiency decreased with temperature for Cl-impregnated ACs. According to increasing chemical content, the surface area decreased and the morphology of carbon became more complicated. Both types of impregnated ACs showed reasonable efficiency for gas-phase Hg-0 removal by adsorption. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: SORBENTS; CAPTURE; ADSORPTION; EMISSIONS; MODEL